The neural monitoring of visceral inputs, rather than attention, accounts for first-person perspective in conscious vision. (May 2018) - Tallon-Baudry, Catherine; Campana, Florence; Park, Hyeong-Dong; Babo-Rebelo, Mariana
Abstract: Why should a scientist whose aim is to unravel the neural mechanisms of perception consider brain-body interactions seriously? Brain-body interactions have traditionally been associated with emotion, effort, or stress, but not with the "cold" processes of perception and attention. Here, we review recent experimental evidence suggesting a different picture: the neural monitoring of bodily state, and in particular the neural monitoring of the heart, affects visual perception. The impact of spontaneous fluctuations of neural responses to heartbeats on visual detection is as large as the impact of explicit manipulations of spatial attention in perceptual tasks. However, we propose that the neural monitoring of visceral inputs plays a specific role in conscious perception, distinct from the role of attention. The neural monitoring of organs such as the heart or the gut would generate a subject-centered reference frame, from which the first-person perspective inherent to conscious perception can develop. In this view, conscious perception results from the integration of visual content with first-person perspective.